2022
DOI: 10.1097/pcc.0000000000003080
|View full text |Cite
|
Sign up to set email alerts
|

Video-Recorded In Situ Simulation Before Moving to the New Combined Neonatal/Pediatric Intensive Care Facility: An Observational Study

Abstract: Moving an ICU to a new location is a challenge. The objective of this study was to use in situ simulation to identify potential problems and solutions with the new environment before commencing patient care.DESIGN: Planned, observational video-recorded simulation study using four scenarios: delivery room management of term-neonate; delivery room management of extremely low-birth-weight infant; management and transfer of an infant with respiratory syncytial virus bronchiolitis and apnea; and management and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(55 reference statements)
2
8
0
Order By: Relevance
“…Video is critical to engendering re exivity. In our study, as found by Krammer et al (9), analysis of the video footage not only con rmed problems anticipated by radiographers prior to, and during the simulation, it also shed light on many additional issues. This is because video connects people to their ways of working in new ways, allowing them to see things in a different light (24).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Video is critical to engendering re exivity. In our study, as found by Krammer et al (9), analysis of the video footage not only con rmed problems anticipated by radiographers prior to, and during the simulation, it also shed light on many additional issues. This is because video connects people to their ways of working in new ways, allowing them to see things in a different light (24).…”
Section: Discussionsupporting
confidence: 87%
“…These included, increased risks of exposure to infection, occupational injury and radiation, and interference with communication and X-ray quality. As with other studies, by conducting this investigation prior to the rooms being commissioned, it was possible to minimise the risks of endangering staff and patients (1,9). While some of the issues were identi ed prior to, or during, the in situ simulation, several unforeseen but important issues, across all four areas of risk, were identi ed and articulated only during reviews of video footage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In several of these studies, video analysis for latent safety threats took place after the simulation and debrief, and was conducted by researchers, rather than participants themselves. 9 13 15 A study by Geis et al 16 used video debriefing with participants, but the authors suggested that their study could have been strengthened by involving participants in more in-depth video debrief and analysis. Bender et al 14 mainly used verbal debrief to identify issues, but used video to highlight or clarify particular events.…”
Section: Introductionmentioning
confidence: 99%